(untitled) (The Conference Hub, 2025)
The article says that ideas of “term” and “lexis” are fundamental in linguistic and terminological studies. Though their appearance is similar, these views serve key roles in understanding language as well as communication. This scientific article defines the differences in theory and practice in terms of terms and lexis, providing a comprehensive analysis based on linguistic theories, applied linguistics, and terminological principles. The main distinctions include their function, scope, and application in different domains. This study contributes to a basic understanding of these concepts and their consequences in language studies.